Exaggerated amygdala activation to ambiguous facial expressions is a familial vulnerability factor for posttraumatic stress disorder. (December 2022) - Hinojosa, Cecilia A.; VanElzakker, Michael B.; Hughes, Katherine C.; Offringa, Reid; Sangermano, Lisa M.; Spaulding, Isabella G.; Staples-Bradley, Lindsay K.; Whitman, Ethan T.; Lasko, Natasha B.; Rauch, Scott L.; Orr, Scott P.; Pitman, Roger K.; et al.
Abstract: Objective: Previous research has reported hyperresponsivity in the amygdala and hyporesponsivity in ventral portions of the medial prefrontal cortex to threat-related stimuli in posttraumatic stress disorder (PTSD). Whether such findings generalize to more ambiguous stimuli and whether such brain activation abnormalities reflect familial vulnerabilities, trauma-exposure, or acquired characteristics of PTSD remain unclear. In this study, we measured brain responses to emotionally ambiguous stimuli (i.e., surprised facial expressions) in identical twin pairs discordant for trauma exposure to elucidate the origin of brain activation abnormalities. Methods: Participants with PTSD (n = 12) and their trauma-unexposed identical cotwins (n = 12), as well as trauma-exposed participants without PTSD (n = 15) and their trauma-unexposed identical cotwins (n = 15), passively viewed surprised and neutral facial expressions during functional magnetic resonance imaging (fMRI). Afterward, participants labeled and rated each facial expression on valence and arousal. Results: Amygdala activation to Surprised and Neutral facial expressions (versus Fixation) was greater in the participants with PTSD and their trauma-unexposed identical cotwins without PTSD, compared to the control twin pairs. In contrast, medial frontal gyrus (MFG) activation to Surprised facial expressions (versus Fixation) was diminished in the PTSD group relative to the other three groups. Conclusions: Amygdala hyperresponsivity to emotionally ambiguous facial expressions may be a familial vulnerability factor that increases the likelihood of developing PTSD after experiencing a traumatic event. In contrast, MFG hyporesponsivity may be an acquired characteristic of the disorder.